Pressure‐Tuned Multicolor Emission of 2D Lead Halide Perovskites with Ultrahigh Color Purity - Gao, Fei‐Fei; Song, Haipeng; Li, Zhi‐Gang; Qin, Yan; Li, Xiang; Yao, Zhao‐Quan; Fan, Jia‐Hui; Wu, Xiang; Li, Wei; Bu, Xian‐He (Angewandte Chemie International Edition, 2023)
The chemical diversity and structural flexibility of lead halide perovskites (LHPs) offer tremendous opportunities to tune their optical properties through internal molecular engineering and external stimuli. Herein, we report the wide‐range and ultrapure photoluminescence emissions in a family of homologous 2D LHPs, [MeOPEA]2PbBr4−4xI4x (MeOPEA=4‐methoxyphenethylammonium; x=0, 0.2, 0.425, 0.575, 1) enabled through internal chemical pressure and external hydrostatic pressure. The chemical pressure, induced by the C−H⋅⋅⋅π interactions and halogen doping/substitution strengthens the structural rigidity to give sustained narrow emissions, and regulates the emission energy, respectively. Further manipulation of physical pressure leads to wide‐range emission tuning from 412 to 647 nm in a continuous and reversible manner. This work could open up new pathways for developing 2D LHP emitters with ultra‐wide color gamut and high color purity which are highly useful for pressure sensing. Wide‐range and ultrapure emissions are achieved in 2D lead halide perovskites (LHPs) by combined chemical pressure from halogen doping/substitution and physical pressure from hydrostatic compression. This work demonstrates precise emission tuning and effective color regulation of 2D LHPs by pressure engineering, which would open a new pathway for developing ultrapure emitters and highly sensitive pressure sensors.